2013
DOI: 10.3109/17453674.2013.784660
|View full text |Cite
|
Sign up to set email alerts
|

Alternative bearings in total knee arthroplasty: risk of early revision compared to traditional bearings

Abstract: Background and purpose There is no substantial clinical evidence for the superiority of alternative bearings in total knee arthroplasty (TKA). We compared the short-term revision risk in alternative surface bearing knees (oxidized zirconium (OZ) femoral implants or highly crosslinked polyethylene (HXLPE) inserts) with that for traditional bearings (cobalt-chromium (CoCR) on conventional polyethelene (CPE)). The risk of revision with commercially available HXLPE inserts was also evaluated.Methods All 62,177 pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…In comparing our study findings with single-center studies [6,16], results were similar in not identifying major differences in CoCR-conventional polyethylene versus CoCr-HLXPE bearings. The results of our study also confirm earlier published findings from a large populationbased study with shorter followup [9]. However, our findings differ from those reported by the Australian Orthopedic Association National Joint Replacement Registry, which reported a lower risk of revision in TKAs using HXLPE [4].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In comparing our study findings with single-center studies [6,16], results were similar in not identifying major differences in CoCR-conventional polyethylene versus CoCr-HLXPE bearings. The results of our study also confirm earlier published findings from a large populationbased study with shorter followup [9]. However, our findings differ from those reported by the Australian Orthopedic Association National Joint Replacement Registry, which reported a lower risk of revision in TKAs using HXLPE [4].…”
Section: Discussionsupporting
confidence: 81%
“…Larger, population-based studies have reported inconsistent results in TKA. Inacio et al [9] did not find a difference in cobalt-chromium (CoCr) HXLPE versus conventional polyethylene TKA bearings in a large (n = 62,177) US sample. However, a recent report from the Australian registry [4] found a lower risk of revision for HXLPE versus conventional polyethylene.…”
Section: Introductionmentioning
confidence: 94%
“…Thus far, however, the clinical benefit of XLPE remains unclear. For example, the Kaiser Implant Registry [16] with 62,177 primary TKAs at followups of 1 to 5 years showed no difference in revision surgery between XLPE and conventional PE bearing surfaces. In contrast, the 2014 Annual Report of the Australian Orthopaedic Association National Joint Replacement Registry [1] found primary TKAs with XLPE had a lower rate of revision than those with conventional PE, although this result was confounded by the much smaller amount of XLPE in use and variations in implant design.…”
Section: Introductionmentioning
confidence: 99%
“…The 2015 Annual Report of the Australian Orthopaedic Association National Joint Replacement Registry found a lower rate of revision in patients implanted with crosslinked PE tibial inserts [1]. In contrast, clinical reports with mid-term followup such as those from the Kaiser Implant Registry [18] demonstrated no benefits or differences in revision surgery rates between TKAs with crosslinked PE versus conventional polyethylene inserts [19,20,28]. In a recent shortterm implant retrieval study comparing retrieved crosslinked PE and conventional polyethylene TKA inserts, Liu et al found no difference in polyethylene surface damage between the two materials [24].…”
Section: Introductionmentioning
confidence: 99%